Customer Confusion in the UK Financial Services: The Case of Savings and Investments - Badr, Chafic (2006)
The increased recent attention to the customer confusion phenomenon, in order to examine its detrimental effects on consumers as well as the organisations instigating it, has motivated researchers to investigate its incidence in a number of industries and markets. This paper explores the customer confusion concept in the context of savings and investments in the UK financial services sector. A review of conceptual theories and secondary sources in the financial services facilitated the formation of an interview approach guide in order to investigate confusion among 10 UK savers and investors. The findings, conclusions and implications have been presented.